56‐6: A Wearable Self‐Driven Piezoelectric Sensor Enabling Real‐Time Blood Pressure Estimation. Issue 1 (28th June 2021) - Qian, Ying; Li, Huimin; Li, Anqi; Liu, Xinghui; Wu, Guoxian; Yu, Weikang; Wang, Kai
Abstract : In this article, a flexible wearable impulse wave sensor that utilizes a polyvinylidene fluoride(PVDF) film‐type piezoelectric sensor and an a‐Si:H dual‐gate thin‐film transistor as a buffer is reported. Differing from passive sensors, this active sensor provides signal rectification and amplification, and accurately collect the impulse wave signals with detailed characteristic peaks. We then propose an effective blood pressure estimation neural network method to obtain the blood pressure and extract parameters that are comparable to those from the model with the Advancement of Medical Instrumentation (AAMI).